Diana and Nubia: Princesses of the Amazons - Shannon Hale (DC Comics, 2022)
Diana, Princess of the Amazons was only the beginning: Shannon Hale, Dean Hale, and Victoria Ying team up again to continue the adventure!
Keywords: Mystery -- Mystery